神经肽Y Y1受体拮抗剂促进大鼠BMSCs成骨分化和股骨缺损修复 (Nan Fang Yi Ke Da Xue Xue Bao, 2018)
OBJECTIVE: To investigate the effects of neuropeptide Y (NPY) Y1 receptor antagonist PD160170 in promoting osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) and accelerating healing of femoral defect in rats. METHODS: The third generation of rat BMSCs were treated with PBS (control) or 10(-6), 10(-7), or 10(-8) mol/L NPY Y1 receptor antagonist PD160170. After 7 and 14 days of treatment, the cells were examined for osteogenic differentiation with alkaline phosphatase (ALP) and alizarin red staining. At 7 and 21 days of treatment, the mRNA and protein expressions of collagen type Ⅰ (COLI), osteocalcin (OCN) and Runt-related transcription factor 2 (Runx2) in the cells were detected using q-PCR and Westem Blotting. In a male SD rat model (body weight 300±20 g) of bilateral femoral condyle defects (2.5 mm in diameter), the effect of daily local injection of 0.2 mL PD160170 (10(-6) and 10(-8) mol/L, for 28 consecutive days) in promoting bone defect repair was evaluated with micro-CT scans. RESULTS: ALP and alizarin red staining showed that the BMSCs treated with PD160170, at the optimal concentration of 10(-8) mol/L, contained more intracellular cytoplasmic brown particles and mineralized nodules in extracellular matrix than PBS-treated cells. PD160170 (10(-8) mol/L) significantly up-regulated the mRNA and protein expressions of COLI at day 7 and those of OCN and Runx2 at day 21 (P < 0.05). In the rat models of femoral bone defect, the volume/tissue volume ratio, bone mineral density and the number of bone trabeculae were significantly greater in 10(-6) mol/L PD160170 group than in the control group (P < 0.05), but the bone trabecular thickness (P=0.07) and bone volume (P=0.35) were similar between the two groups. CONCLUSION: NPY Y1 receptor antagonist PD160170 can promote osteogenic differentiation of BMSCs and healing of femoral defects in rats, suggesting the potential of therapeutic strategies targeting NPY Y1 receptor signaling in the prevention and treatment of bone fracture and osteoporosis.